KONTRIBUSI PENDAPATAN PEREMPUAN TERHADAP PENDAPATAN RUMAHTANGGA (Studi Pasar Sentral Majene Sulawesi Barat) - Dahlia Dahlia (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
The purpose of this study was to determine the effect of female traders' income on household income in Majene Central Market, West Sulawesi. To determine the effect of female traders' income on household income in Majene Central Market, West Sulawesi, a simple linear regression test was conducted. The results showed that the income of female traders had a positive and significant effect on household income in Majene Central Sulawesi, West Sulawesi.